RANCANG BANGUN SISTEM INFORMASI E-LEARNING BERBASIS WEB (STUDI KASUS MI AL-INAYAH DARMINIYAH) - Indri, Indri Mulyani; Vany Terisia; Muhajir Syamsu (ITB Ahmad Dahlan Jakarta, 2023)
Learning is a process of interaction between educators and students where educators provide knowledge to grow at once develop insight, creativity and mindset of students. website-based e-learning to support the learning process teaching at MI Al-Inayah Darminiyah which can make it easier for students to learn and provide flexibility to be able to receive learning materials where and anytime without face-to-face contact with the teacher. The method used is the method and UML (Unified Modeling Language) and built using the PHP programming language (Hypertext Preprocessor) and using MySQL as database server as well XAMPP as a web server. Data collection through interviews with teachers and school staff as well as make observations which are then carried out by research literature. The result is that the e-learning website can be used by the admin, teachers and students at MI Al-Inayah Darminiyah in supporting the learning process teaching at the moment. Admins can manage teacher and student accounts, teachers can easily manage the material and assignments submitted. Student with easily get school notifications as well as materials and assignments delivered by the teacher. This e-learning website helps schools to improve processes learning optimally so that it can further affect improvement academic student achievement because of the convenience for students in accessing the media learning anytime and anywhere in accordance with the school's vision of